Monogenic causation of pediatric nephrolithiasis - Schott, Clara; Pourtousi, Ava; Connaughton, Dervla M. (Frontiers in Urology, 2022)
Nephrolithiasis is a condition in which crystals precipitate out of the urine forming kidney stones in the renal calyces and pelvis. Approximately 80% of stones are composed of calcium oxalate and calcium phosphate. In recent years, there has been a significant increase in the prevalence of nephrolithiasis across populations, specifically in the pediatric population. The etiology of stone disease is multifactorial, and includes environmental, dietary, hormonal, and genetic factors. Evidence for monogenic causation (also known as Mendelian or single-gene disorders) in nephrolithiasis includes the finding that 30% of children with stone disease report a positive family history, with monogenic nephrolithiasis accounting for approximately 30% of cases. Monogenic nephrolithiasis can occur in isolation or may be the result of an underlying genetic disorder including autosomal dominant hypocalcemia (ADH), primary hyperoxalurias, and hereditary hypophosphatemic rickets with hypercalciuria (HHRH), to name a few. Currently, there are 41 known genes that represent monogenic causes of human nephrolithiasis. Since early detection of these mutations can in some cases prevent the progression to end stage kidney disease in pediatric patients, establishing the genetic basis for nephrolithiasis is increasingly important. Here we provide an overview of kidney stone disease in children with a focus on monogenic causation in the pediatric population.